2015
DOI: 10.1097/qai.0000000000000578
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Routine Opt-Out HIV Testing and Linkage to Care Program for Previously Diagnosed Patients in Publicly Funded Emergency Departments in Houston, TX

Abstract: Background The Routine Universal Screening for HIV (RUSH) program provides opt-out HIV testing and linkage to care for emergency department (ED) patients in Harris Health System, Houston, TX. Seventy-five percent of patients testing positive in this program have been previously diagnosed. Whether linkage to care is increased among these patients is unknown. Methods We conducted a retrospective cohort study of persons tested for HIV in the ED between 2008–2012 but had a previously documented positive HIV test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Reengagement studies reported on 8 different outcomes; three of the four studies reported viral load or viral suppression as one of their outcomes. Three of these four studies found significant improvements in engagement in care following the intervention, though these significant impacts included a range of effect sizes (such as a 5% increase in re-linkage [24], 11.2% increase in viral suppression [25], and 3.9–5.4% reduction in no care in the past 6 months [26]).…”
Section: Resultsmentioning
confidence: 99%
“…Reengagement studies reported on 8 different outcomes; three of the four studies reported viral load or viral suppression as one of their outcomes. Three of these four studies found significant improvements in engagement in care following the intervention, though these significant impacts included a range of effect sizes (such as a 5% increase in re-linkage [24], 11.2% increase in viral suppression [25], and 3.9–5.4% reduction in no care in the past 6 months [26]).…”
Section: Resultsmentioning
confidence: 99%
“…Data from testing programs support the notion that repeat positive tests are an ongoing issue. 16,17 Presumably, this indicates that a proportion of patients do not receive their initial test results and/or they are not comfortable revealing their diagnosis to treating physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Another source of identifying patients was the BTGH emergency center’s routine HIV testing program. Routine screening helped identify persons with HIV infection, including many diagnosed elsewhere but not known positive in our system 19 . These latter recruitment methods were most fruitful when persons were newly diagnosed with HIV infection during the course of their hospital stay, since the census review focused on what was known at the time of admission.…”
Section: Discussionmentioning
confidence: 99%